Phytoplankton Composition in White Shrimp (Litopenaeus vannamei) Pond Culture Infected White Feces Disease (WFD) - Anjaini, Jefri; Simangunsong, Tohap; Fadjar, Mohamad (Research Journal of Life Science, 2023)
The aim of this study is to find out the composition and condition of phytoplankton in the white shrimp (L. vannamei) culture inffected by the white feces disease so that one of the indicators of the onset of the white feces disease can be known. This research uses descriptive methods. The observed parameters are the identification of species diversity, abundance, diversity index and dominance index of phytoplankton. The sampling was conducted at three locations, Tuban area, Situbondo area, Lamongan area. The results of the study showed observations in Lamongan area, the total abundance of phytoplankton was 473 cells/L. Situpondo areas abundantity of phytoplankton total was 633 cels/L and Tuban areas abundance was 887 cells/L. In Lamongan area, the diversity index was 1,009. In Situbondo areas diversity Index was 1,013. In Tuban area, diversity indexes were 1,082. In Lamongan area, a dominance index was 0.477. In Situpond area, it was obtained a domination index of 0.544. The genus that dominates the three ponds are Cyclotella and Navicula. At all three locations have high variety of species and abundance of the genus members of the filum Cyanophyta and Bacillariofhyta are detrimental, the genuses that are found are indicators of contaminated waters. The dominance of Cyanophyta (blue-green algae) is also an indicator of the White Feces Disease.